Staff Note for the G20 : The Role of the SDR. (Policy Papers; Policy Paper ;, 2016)
Following the recent diagnostic of the international monetary system (IMS), the IMF will explore whether a broader role for the SDR could contribute to its smooth functioning. The economic rationale for or against broader use of the SDR will be examined, focusing in particular on identifying any gaps and market failures the SDR could help address in light of the increasingly multi-polar nature of the global economy and growing financial interconnectedness. This note sets out some initial considerations on this matter. The note sketches some key issues bearing on the role of the SDR in each of three concepts: (i) the official SDR, or 'O-SDR', the composite reserve asset issued and administered by the IMF; (ii) SDR-denominated financial market instruments, or 'M-SDRs,' which could be both issued and held by any parties; and (iii) the SDR as a unit of account. M-SDRs reduce foreign exchange and interest rate risk relative to single-currency instruments, but there are some drawbacks and challenges. The basket nature of M-SDRs would allow the volatility of returns to be lower than for a similar singlecurrency instrument. However, the SDR only represents one of many possible sets of portfolio weights, and issuers or investors could use existing instruments to replicate their preferred weights at a relatively low cost. There are also challenges to market development, including settling and clearing of M-SDR transactions, dealing with potential basket redefinition, and fostering secondary market trading in order to generate liquidity and market depth. There are potential benefits to using the SDR as a unit of account, which have to be weighed against other considerations. Publishing economic statistics and financial statements in SDR terms could help users identify valuation changes. Statistical authorities would need to invest in communicating the rationale for any change in practices. While the official SDR under its current framework is not playing a significant role in the IMS, a re-examination of its role is expected to inform whether any specific reform options should be pursued. The evolution of the IMS has given rise to an active debate on how much concern is posed by high rates of reserve accumulation, global imbalances, and rising claims on reserve issuers, and on whether the O-SDR could contribute to addressing these issues.